Improving The Incentive System For Educational Institutions - Abdurahimova Salomatposhsha (Genius Journals, 2025)
This article examines current issues related to the effectiveness of the current remuneration system for faculty members at higher education institutions and develops scientific recommendations for creating a system that stimulates their work activity and ultimately increases the effectiveness of their research and teaching activities.
Keywords: Higher education; work motivation